PERCEPTION OF DPMPTSP DIY CIVIL SERVANTS REGARDING THE ESTABLISHMENT OF A PROFESSIONAL ORGANIZATION FOR THE FUNCTIONAL POSITION OF INVESTMENT MANAGEMENT IN THE SPECIAL REGION OF YOGYAKARTA - Fitriana Pujiastuti; Muhammad Fajrus Shodiq (Journal of Social Politics and Governance (JSPG), 2026)
The current investment climate in Indonesia is still hampered by several obstacles that must be overcome. In this regard, a platform is needed to encompass the functional position of investment management in competency development. This study aims to understand the perceptions of Civil Servants of the Investment and One-Stop Integrated Service Office of the Special Region of Yogyakarta regarding the formation of a professional organization for the functional position of investment management in the Special Region of Yogyakarta. This study uses perception theory and a qualitative method, including interviews and documentation. The study's results show that the formation of a professional organization for the functional role of investment management is considered a positive development. The establishment of this professional organization is expected to serve as a forum for professionals to develop competencies, enhance professionalism, provide advocacy, and offer networking opportunities. Therefore, in its implementation, it needs to be carefully planned and managed sustainably so that it provides tangible, positive benefits without burdening functional positions, thereby maintaining performance.